2009
DOI: 10.1097/qad.0b013e32832ac34e
|View full text |Cite
|
Sign up to set email alerts
|

The public health approach to identify antiretroviral therapy failure: high-level nucleoside reverse transcriptase inhibitor resistance among Malawians failing first-line antiretroviral therapy

Abstract: Background Over 150 000 Malawians have started antiretroviral therapy (ART), in which first-line therapy is stavudine/lamivudine/nevirapine. We evaluated drug resistance patterns among patients failing first-line ART on the basis of clinical or immunological criteria in Lilongwe and Blantyre, Malawi. Methods Patients meeting the definition of ART failure (new or progressive stage 4 condition, CD4 cell count decline more than 30%, CD4 cell count less than that before treatment) from January 2006 to July 2007 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
240
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(271 citation statements)
references
References 23 publications
27
240
4
Order By: Relevance
“…In adults, the criteria have been shown to be insensitive measures for virologic outcomes [10,11], and a high prevalence of ARV resistance mutations has been documented in HIV-infected adults by the time they progress to meet the WHO criteria for ARV therapy switch [12]. A recent report showed same similarity in pediatric WHO guidelines, where it has been found to offer an insensitive measure of virologic failure [13].…”
Section: Research Articlementioning
confidence: 99%
“…In adults, the criteria have been shown to be insensitive measures for virologic outcomes [10,11], and a high prevalence of ARV resistance mutations has been documented in HIV-infected adults by the time they progress to meet the WHO criteria for ARV therapy switch [12]. A recent report showed same similarity in pediatric WHO guidelines, where it has been found to offer an insensitive measure of virologic failure [13].…”
Section: Research Articlementioning
confidence: 99%
“…Frequent misclassification of virological failure in adult patients has been reported, leading to early ART switch or late failure diagnosis. [3][4][5] In the latter circumstances, by the time treatment failure is recognized, patients may have already accumulated drug resistance mutations and high-level cross-resistance to subsequent antiretroviral regimens. [6][7][8] Minimizing resistance is particularly important in RLS with limited ART options, usually restricted to first-line nonnucleoside reverse transcriptase inhibitor (NNRTI)-based and second-line protease inhibitor (PI)-based regimens.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the mutational pathways to drug resistance to nucleoside reverse transcriptase inhibitor (NRTI) drugs may vary among different HIV-1 subtypes. [9][10][11][12][13][14] In addition, non-B subtype HIV genomes carry subtype-specific polymorphisms that act as minor mutations in subtype B, particularly in the protease gene. [15][16][17] The impact of these genetic differences on the clinical response to antiretroviral therapy has yet to be fully assessed.…”
Section: Introductionmentioning
confidence: 99%